A Review of English Writing Acquisition in China: a Perspective Based on Error Analysis and the Motivational Strategies of Students - Wang, Yan (Trinity College (Dublin, Ireland). School of Education, 2022)
Writing is an important expressive and output skill in English language acquisition and is one of the criteria for measuring students' English language ability. As an output skill, English writing has always been an area in which Chinese learners of English are less adept. How to improve the efficiency of Chinese learners' English writing acquisition and improve the way English writing is taught has been an issue of importance to many experts and scholars. In this thesis, a dozen recent studies in China were selected from a large database of papers to summarise the main writing errors made by English learners in some regions and schools in China, as well as the main self-regulation strategies and types of motivation adopted by these students in their learning process. The analysis and explanation of these phenomena were based on both external and internal influences. The results of the study show that Chinese learners' writing errors are mainly in the areas of vocabulary collocation and grammar related, due to the general influence of native language transfer. Similarly, Chinese English learners' instrumental motivation is prevalent due to the overall educational and social environment in China, with certificate motivation being the most important instrumental motivation. It is also for this reason that social-behaviour strategies and avoidance strategies are most common among English writing learners. In addition to language transfer, cultural differences between Chinese and English, as well as different language conventions, also influence the occurrence of errors. The importance that teachers attach to this aspect of errors also affects the frequency of errors made by students. In addition, the educational environment is a major factor influencing Chinese learners' personal motivation and learning strategies, including family, school and society. There are also some internal influences, such as self-avoidance due to writing anxiety.
Keywords: Language Education; Education